The house of the dead - Dostoyevsky, Fyodor, 1821-1881.; Garnett, Constance, 1861-1946. (Mineola, N.Y. : Dover Publications, 2004)
Accused of political subversion as a young man, Dostoyevsky was sentenced to four years of hard labor at a Siberian prison camp--a horrifying experience from which, years later, he developed this semi-autobiographical memoir of a man condemned to penal servitude for murdering his wife. Describing in relentless detail the physical and mental suffering of the convicts, this haunting and remarkable work ranks among Dostoyevsky's greatest masterpieces.
Originally published: New York : Macmillan, 1915.
Keywords: Exiles -- Russia (Federation) -- Siberia -- Fiction; Prisoners -- Russia (Federation) -- Siberia -- Fiction